First Results From a Propensity Matching Trial of Mycophenolate Mofetil vs. Azathioprine in Treatment-Naive AIH Patients - Dalekos, George N.; Arvaniti, Pinelopi; Gatselis, Nikolaos K.; Samakidou, Anna; Gabeta, Stella; Rigopoulou, Eirini; Koukoulis, George K.; Zachou, Kalliopi (Frontiers in Immunology, 2022)
Background/Aims: As previous real-world studies and metanalyses have shown that mycophenolate mofetil (MMF) might have better efficacy than azathioprine (AZA) in autoimmune hepatitis (AIH), we conducted a propensity matching study to assess the efficacy and safety of MMF vs. AZA. Methods: All 126-consecutive treatment-naïve adult AIH patients, diagnosed and followed in our department since 2016, were included. Patients received prednisolone 0.5-1mg/kg/day plus either AZA 1-2mg/kg/day or 1.5-2g/day MMF. The tapering of prednisolone was identical between groups. Results: After propensity matching score and adjustment for known factors affecting response to treatment and outcome, 64 patients were included in the study (MMF=32 and AZA=32). Rates of non-response, complete biochemical response (CBR) at 6- and 12-months and prednisolone withdrawal (6-months, 12-months, and end of follow-up) were identical between groups. However, MMF treatment was significantly associated with CBR at the end of follow-up (OR 11.259; 95%CI: 1.3-97.4, p=0.028). AZA patients were more prone to stop treatment due to AZA intolerance/insufficient response (p=0.0001). At the end of follow-up, the overall efficacy of each schedule was also significantly higher in the MMF group compared to the AZA group (p=0.0001). Conclusion: We showed for the first time in a propensity matching study that MMF can be used as first-line therapy in AIH as attested by the significantly higher CBR at end of follow-up compared to AZA. If this better efficacy is also associated with higher histological remission rates and sustained CBR off immunosuppression needs further evaluation.